SOSIALISASAI PERHITUNGAN HARGA POKOK PENJUALAN DAN HARGA JUAL PRODUK PADA PELAKU UMKM DI DESA SADE KABUPATEN LOMBOK TENGAH - Utami, Luh; Azzindani, Rahmatia; Suandi, Suandi; Pahmi, Saepul; Wardhani, Kania; Algifari, Muhammad Daelami (LPPM Institut Pendidikan Nusantara Global, 2024)
Small and medium businesses have an important role as drivers of the economy in Indonesia. However, various obstacles that arise can hinder its development, especially problems in the financial sector. MSMEs' difficulties in determining the cost of goods sold and selling prices can affect their profits and business sustainability. The outreach was carried out to provide knowledge and understanding for MSME players so they can calculate the cost of goods sold and selling prices correctly. This community service activity was carried out in Sade Village, Central Lombok Regency, which was attended by MSME actors in the tourist village. The aim of this service is to provide knowledge and understanding for MSMEs in determining the cost of goods sold and the selling price of products. This activity was carried out on March 6 2024. The results of the activity showed that the socialization provided could provide positive benefits for participants. This can be seen from the alignment of the material presented with the participants' needs as well as the participants' enthusiasm in participating in this activity.